Resistance Mechanisms of Plant Pathogenic Fungi to Fungicide, Environmental Impacts of Fungicides, and Sustainable Solutions - Tarequl Islam; Danishuddin; Noshin Tabassum Tamanna; Muhammad Nurul Matin; Hasi Rani Barai; Md Azizul Haque (Plants)
The significant reduction in agricultural output and the decline in product quality are two of the most glaring negative impacts caused by plant pathogenic fungi (PPF). Furthermore, contaminated food or transit might introduce mycotoxins produced by PPF directly into the food chain. Eating food tainted with mycotoxin is extremely dangerous for both human and animal health. Using fungicides is the first choice to control PPF or their toxins in food. Fungicide resistance and its effects on the environment and public health are becoming more and more of a concern, despite the fact that chemical fungicides are used to limit PPF toxicity and control growth in crops. Fungicides induce target site alteration and efflux pump activation, and mutations in PPF result in resistance. As a result, global trends are shifting away from chemically manufactured pesticides and toward managing fungal plant diseases using various biocontrol techniques, tactics, and approaches. However, surveillance programs to monitor fungicide resistance and their environmental impact are much fewer compared to bacterial antibiotic resistance surveillance programs. In this review, we discuss the PPF that contributes to disease development in plants, the fungicides used against them, factors causing the spread of PPF and the emergence of new strains, the antifungal resistance mechanisms of PPF, health, the environmental impacts of fungicides, and the use of biocontrol agents (BCAs), antimicrobial peptides (AMPs), and nanotechnologies to control PPF as a safe and eco-friendly alternative to fungicides.